Assessing the influence of fuel geometrical shape on fire dynamics simulator (FDS) predictions for a large-scale heavy goods vehicle tunnel fire experiment. (May 2016) - Wang, Xiaoyun; Fleischmann, Charles; Spearpoint, Michael
Highlights: A large-scale HGV fuel package is represented through four different simplified geometrical shapes in FDS. The predictions of flame extension are affected by the use of different fuel geometrical shapes. The predicted temperature distributions are significantly affected when no large targets is located downstream of the fire, while only weak influences on the temperatures are found in the presence of a large target. Different gas distribution profiles are obtained when a 2D gas burner on the top of the fuel package scenario is applied. Abstract: This paper uses four different simple geometrical shapes to simulate a large-scale heavy goods vehicle (HGV) tunnel fire experiment using Fire Dynamics Simulator, version 6 (FDS6) in order to investigate the influence of using different fuel package shapes. Simulations also investigate the influence on temperature profiles when a large target is placed downstream of the fuel package. Predictions of flame extension, temperature profiles and gas species concentrations are compared with the experimental data. The use of the geometrical shapes causes significant differences in flame extension lengths during the fully developed fire phase. The variation in temperature predictions caused by using the different fuel shapes are insignificant when a large target is present behind the fire, however this is not the case if the target is omitted especially during the fully developed phase.